Genomic characterization of environmental Klebsiella pneumoniae through whole genome sequencing - Sharmin, Mehbooba (Brac University, 2024)
This thesis submitted to the Department of Mathematics and Natural Sciences in partial fulfillment of the requirements for the degree of Master of Science in Biotechnology, 2024.